Screening for colorectal cancer and advanced colorectal neoplasia in kidney transplant recipients: cross sectional prevalence and diagnostic accuracy study of faecal immunochemical testing for haemoglobin and colonoscopy. (25th July 2012) - Collins, Michael G; Teo, Edward; Cole, Stephen R; Chan, Choy-Yoke; McDonald, Stephen P; Russ, Graeme R; Young, Graeme P; Bampton, Peter A; Coates, P Toby
Abstract : Objective To investigate whether screening kidney transplant recipients aged over 50 years for colorectal cancer with a faecal immunochemical test for haemoglobin might be justified, by determining the prevalence of advanced colorectal neoplasia and evaluating the diagnostic accuracy of faecal haemoglobin testing compared with colonoscopy in a population of kidney transplant recipients at otherwise average risk. Design Cross sectional prevalence and diagnostic accuracy study with index test of faecal haemoglobin and reference standard of colonoscopy. Setting Outpatient clinics in metropolitan and regional hospitals in South Australia. Participants 229 kidney transplant recipients aged 50 years and over, who were at least 6 months (mean 9.0 (SD 8.4) years) post-transplant and otherwise at average risk of colorectal cancer, completed the study between June 2008 and October 2011. Interventions Faecal immunochemical testing (Enterix Insure) for human haemoglobin, followed by colonoscopy with histological evaluation of retrieved samples. Main outcome measures Prevalence of advanced colorectal neoplasia, defined as an adenoma at least 10 mm in diameter, villous features, high grade dysplasia, or colorectal cancer; sensitivity, specificity, and predictive values of faecal haemoglobin testing for advanced neoplasia compared with colonoscopy. Results Advanced colorectal neoplasia was found in 29 (13%, 95% confidence interval 9% to 18%) participants, including 2% (n=4) with high grade dysplasia and 2% (n=5) with colorectal cancer. Faecal testing for haemoglobin was positive in 12% (n=28); sensitivity, specificity, and positive and negative predictive values for advanced neoplasia were 31.0% (15.3% to 50.8%), 90.5% (85.6% to 94.2%), 32.1% (15.9% to 52.4%), and 90.1% (85.1% to 93.8%). Colonoscopy was well tolerated, with no significant adverse outcomes. To identify one case of advanced neoplasia, 8 (6 to 12) colonoscopies were needed. Conclusions Kidney transplant recipients aged over 50 years have a high prevalence of advanced colorectal neoplasia. Faecal haemoglobin screening for colorectal neoplasia has similar performance characteristics in transplant recipients to those reported in general population studies, with poor sensitivity but reasonable specificity. Surveillance colonoscopy might be a more appropriate approach in this population. Trial registration Australian New Zealand Clinical Trials Registry ACTRN12608000154303.